2005
DOI: 10.1016/j.febslet.2005.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Wobble modification deficiency in mutant tRNAs in patients with mitochondrial diseases

Abstract: Point mutations in mitochondrial (mt) tRNA genes are associated with a variety of human mitochondrial diseases. We have shown previously that mt tRNA(Leu(UUR)) with a MELAS A3243G mutation and mt tRNA(Lys) with a MERRF A8344G mutation derived from HeLa background cybrid cells are deficient in normal taurine-containing modifications [taum(5)(s(2))U; 5-taurinomethyl-(2-thio)uridine] at the anticodon wobble position in both cases. The wobble modification deficiency results in defective translation. We report here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…Interestingly, a recent report suggested that taurine could critically affect mitochondrial function. Yasukawa et al [46] found two novel taurine-containing modified uridines in human mitochondrial DNA. When the uridine modifications were not present, defective mitochondrial function occurred and diseases such as mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes (MERRF) syndrome and myoclonic epilepsy with ragged red fibres (MELAS) syndrome may ensue.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent report suggested that taurine could critically affect mitochondrial function. Yasukawa et al [46] found two novel taurine-containing modified uridines in human mitochondrial DNA. When the uridine modifications were not present, defective mitochondrial function occurred and diseases such as mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes (MERRF) syndrome and myoclonic epilepsy with ragged red fibres (MELAS) syndrome may ensue.…”
Section: Discussionmentioning
confidence: 99%
“…In line with a role of the thiolation in the tRNAs binding to their cognate codons, the absence of S 2 U in mitochondria results in impaired mitochondrial protein synthesis, which leads to reduced respiratory activity and human pathologies including MERFF (myoclonus epilepsy associated with ragged-red fibers), a subgroup of the mitochondrial encephalomyopathies where the mitochondrial tRNA LYS lacking the wobble modification cannot translate either of its codons (AAA and AAG) (13,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been suggested by which the A3243G mutation could alter mitochondrial translation, and the contribution of each mechanism may differ depending on the nuclear background (Jacobs 2003). A3243G mutant tRNA Leu(UUR) lacks the 5-taurinomethyl uridine (tm 5 U) normally present at the anticodon wobble base, U34 (Yasukawa et al 2000(Yasukawa et al , 2005Suzuki et al 2002), and displays decreased in vitro translation of poly(UUA) and greatly decreased translation of poly(UUG) mRNAs (Kirino et al 2004). Mutant cells have decreased steady-state levels of tRNA Leu(UUR) (Chomyn et al 1992(Chomyn et al , 2000Janssen et al 1999;Yasukawa et al 2000;Park et al 2003) and frequently reductions in the fraction of tRNA Leu(UUR) that is aminoacylated (El Meziane et al 1998;Janssen et al 1999;Borner et al 2000;Chomyn et al 2000;Park et al 2003).…”
Section: Discussionmentioning
confidence: 99%